A genetic algorithm for the simultaneous delivery and pickup problems with time window - Wang, Hsiao-Fan; Chen, Ying-Yen (Computers & industrial engineering, 2012)
► A vehicle routing problem with simultaneous delivery and pickup problems with time windows is considered. ► A mixed binary integer programming model denoted by SDPPTW is formulated. ► A co-evolution genetic algorithm is developed for solution. ► Evaluation of accuracy and efficiency is done. This paper concerns a Simultaneous Delivery and Pickup Problem with Time Windows (SDPPTW). A mixed binary integer programming model was developed for the problem and was validated. Due to its NP nature, a co-evolution genetic algorithm with variants of the cheapest insertion method was proposed to speed up the solution procedure. Since there were no existing benchmarks, this study generated some test problems which revised from the well-known Solomon’s benchmark for Vehicle Routing Problem with Time Windows (VRPTW). From the comparison with the results of Cplex software and the basic genetic algorithm, the proposed algorithm showed that it can provide better solutions within a comparatively shorter period of time.